Sebuah Jurnal Audit Audit Plan, Audit Program dan Audit Prosedur Pada Harta, Utang dan Modal: Audit Plan, Audit Program, Audit Prosedur, Harta, Utang, Modal - Novianty - (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2020)
The purpose of this study is to find out how the audit plan, audit program and audit procedures and procedures on assets, debt and capital. This research is also intended to find out whether inventory is evaluated by company management at all times and how to audit the inventory system in the midst of the rise of online systems has been widely used today. The research method used in this research is a descriptive analysis method which is done by discussing all the material or theory of the Audit Plan, Program Audit and Audit Procedures on Assets, Debt and Capital by referring to the applicable audit standards and procedures. The results of this study indicate that auditors and public accountants must conduct a preliminary survey of the data or identity of the company to be audited before conducting an audit plan, program audit and audit procedures. Audit plan, program audit and audit procedures must be prepared and carried out as well as possible in order to produce a good audit quality so that in the end it will produce a good audit report as well. Keyword: Audit Plan, Audit Program, Audit Prosedur, Aktiva, Liabilities and Common Stock